Digital transformation COVID-19 era: startup strategies for technology, management, and people - De Leon, Frediezel G.; Sedero, Mary Ann T.; Antiquiera, Marianne Feliz R.; Silvederio, Megara Juliene P.; Sara, Angela R. (International Journal of Advances in Applied Sciences, 2025)
Startups are not an exception to the fast acceleration of digital transformation across sectors caused by the COVID-19 pandemic. Digital transformation has served as a strategic lever for startups to improve operations, enhance customer experiences, and develop new business models. This study investigates how startups in Western Visayas, Philippines, navigated the pandemic while undergoing digital transformation. Our primary objective is to provide a comprehensive understanding of digital transformation, outlining its key components. By analyzing relevant business literature, we identified three core areas: i) technology, ii) management, and iii) people. This research explores the strategies employed by startups to embrace digital transformation, the technological tools they utilize, and the critical role of effective leadership and organizational culture in successful transformation initiatives. Data was collected through an online survey administered on Qualtrics. The findings reveal that most startups adapted their business models, leveraged social media platforms, and relied on their customer base for support during the pandemic. This study contributes to the existing knowledge base by offering insights into the digital transformation landscape in the Philippines. Furthermore, it enhances our understanding of the strategies and processes required to address the challenges of the digital age.